Experimental investigation to compare the modulus of rupture in high strength self compacting concrete deep beams and high strength concrete normal beams - Mohammadhassani, M.; Jumaat, Mohd Zamin; Jameel, M. (Elsevier, 2012)
This paper investigates and compares the cracking moment and modulus of rupture in deep and normal beams. Eight high-strength-self-compacting concrete (HSSCC) deep beams and nine high-strength concrete (HSC) normal beams are casted and tested. The results from ACI 318-95 and CSA-94 codes show the discrepancies in values of modulus of rupture for HSSCC deep and normal beams. These differences are due to non-consideration of load transfer mechanism in deep beams and high strength of concrete. Based on the present study ACI 318-95 is recommended for calculating modulus-of-rupture in HSSCC deep beams whereas CSA-94 is suggested for HSC normal beams.